Identifying solid luminogens through gold-catalysed intramolecular hydroarylation of alkynes - Shaikh, Aslam C.; Shalini, S.; Vaidhyanathan, Ramanathan; Mane, Manoj V.; Barui, Ayan Kumar; Patra, Chitta Ranjan; Venkatesh, Yeduru; Bangal, Prakriti Ranjan; Patil, Nitin T. (European Journal of Organic Chemistry, 2015)
The identification of a new class of luminogens based on pyrrolo-quinoxaline embedded coumarin (PQC) structures is reported. The reaction relies on the gold-catalyzed hydroarylation reaction of appropriately substituted aryl alkynoates that produces molecules that exhibit solvatochromism and aggregation-induced emission enhancement (AIEE) phenomena. The application of PQCs for live cell imaging has also been demonstrated.
Keywords: Cell imaging; Dyes/pigments; fluorescence; Gold; Luminescence; Solvatochromism